Answer:
y= -2x-5
Explanation:
First find the gradient of the first line
![m = (y2 - y1)/(x2 - x1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wxaq0o1duauvydc64eh9k4q6hs64eo99ss.png)
m=
![(1 - - 3)/(4 - - 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/inswy4qy50sb04o2e7g533rilrp2s3g6lc.png)
m=
![(4)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3i8mr1agujino9g4u7r6lra9sbj7cg9l3d.png)
m=1/2
From this we can find the gradient of the perpendicular line, or the normal.
m1 × m2 = -1
Replace m1 with 1/2
1/2 × m2 = -1
m2= -2
Substitute values into
y-y1=m (x-x1)
y-3=-2 (x+4)
y-3=-2x -8
y=-2x-5